Efficacy and safety of fixed‐dose combination therapy, alogliptin plus metformin, in Asian patients with type 2 diabetes: A phase 3 trial. Issue 5 (22nd February 2017) - Ji, Linong; Li, Ling; Kuang, Jian; Yang, Tao; Kim, Dong‐Jun; Kadir, Azidah A.; Huang, Chien‐Ning; Lee, Douglas
Abstract : This study evaluated the efficacy and safety of 26 weeks of twice‐daily (BID) alogliptin + metformin fixed‐dose combination (FDC) therapy in Asian patients with type 2 diabetes. Patients aged 18 to 75 years with hemoglobin A1c (HbA1c) of 7.5% to 10.0% after ≥2 months of diet and exercise and a 4‐week placebo run‐in were enrolled. Eligible patients were randomized (1:1:1:1) to placebo, alogliptin 12.5 mg BID, metformin 500 mg BID or alogliptin 12.5 mg plus metformin 500 mg FDC BID. The primary endpoint was change in HbA1c from baseline to end of treatment (Week 26). In total, 647 patients were randomized. The least‐squares mean change in HbA1c from baseline to Week 26 was −0.19% with placebo, −0.86% with alogliptin, −1.04% with metformin and −1.53% with alogliptin + metformin FDC. Alogliptin + metformin FDC was significantly more effective ( P  < .0001) in lowering HbA1c than either alogliptin or metformin alone. The safety profile of alogliptin + metformin FDC was similar to that of the individual components alogliptin and metformin. The study demonstrated that treatment with alogliptin + metformin FDC BID resulted in better glycaemic control than either monotherapy and was well tolerated in Asian patients with type 2 diabetes.